An Evaluation of the Cultural Elements within Malaysian Year 1 English Textbooks: KSSR SK English Year 1 and CEFR Super Minds 1 (Sains Humanika, 2022)
The purpose of this study is to evaluate the cultural elements of the new Malaysian Year 1 English Textbook, CEFR Super Minds 1 in comparison to the old KSSR SK English Year 1 textbook from the teachersâ€™ perspectives. This study also attempts to find out the teachersâ€™ opinions regarding the inclusion of local and foreign culture in the English textbook and to identify their preferred textbook among the two textbooks. The sample of the study is 30 English school teachers teaching Year 1 and 2 in the Johor State. A mixed-method research design was used to carry out the research. The instruments used were Likert scale checklist items and open-ended survey questions. The findings revealed that the teachers who participated in the study preferred the old textbook, KSSR SK English Year 1 over the new CEFR Super Minds 1 textbook. However, teachers also believed that while elements of local culture were important and necessary, the inclusion of foreign culture also has its benefits.Â
Keywords: Textbook evaluation; Cultural elements; Year 1 English Textbooks; Malaysia